Improving the evidence base for better comparative effectiveness research. (September 2015) - Brophy, James M
The last 20 years has documented that the evidence base for informed clinical decision-making is often suboptimal. It is hoped that high-quality comparative effectiveness research may fill these knowledge gaps. Implicit in these changing paradigms is the underlying assumption that the published evidence, when available, is valid. It is posited here that this assumption is sometimes questionable. However, several recent methods that may improve the design and analysis of comparative effectiveness research have appeared and are discussed here. Examples from the cardiology literature are provided, but it is believed the highlighted principles are applicable to other branches of medicine.